Impacting Factors of College Students’ Satisfaction with Leadership Education in Jiaxing, China - Liu, Jijun (Scholar: Human Sciences, 2025)
Purpose: This study explores the factors influencing students’ satisfaction with leadership education in a public university in Jiaxing, China with the following five independent variables (academic experience, campus life, social integration, learning material, career progress, and perceived quality of teaching) on the dependent variables (students’ satisfaction). Research design, data, and methodology: The research employed a Cronbach’s Alpha in a pilot test (n=30) for reliability and the Index of Item-Objective Congruence (IOC) for validity. Multiple linear regression was used to assess 106 valid replies from students at a public university in Jiaxing, China, to confirm the existence of a significant association between the variables. After that, 30 students participated in a 12-week strategic planning (SP). The quantitative findings from the pre-SP and post-SP were then compared using the paired-sample t-test. Results: The study found that academic experience, course content, and teachers’ perceived quality all impacted students’ happiness by multiple linear regression but that campus life, social integration, and professional advancement had no discernible effect on creativity. It is important to note that students’ satisfaction was highly impacted by their academic background, the content they learned, and how well they thought their teachers were doing. Conclusions: The comparison’s paired-sample t-test results showed a substantial change in students’ satisfaction between the pre-SP and post-SP phases.